Azithromycin: An Underappreciated Quinolone-Sparing Oral Treatment for Pseudomonas aeruginosa Infections - Erlinda R. Ulloa; George Sakoulas (MDPI AG, 2022)
Outpatient treatment of Pseudomonas aeruginosa infections is challenged by increasing rates of resistance to fluoroquinolones, the only class of antibiotics which offers an established oral route of administration against this organism. Azithromycin does not demonstrate activity against P. aeruginosa when evaluated under standard methods of susceptibility testing with bacteriologic media. However, growing evidence shows that azithromycin is very active against P. aeruginosa when using physiologic media that recapitulate the in vivo milieu and is supported by animal models of infection and various clinical settings, including cystic fibrosis. We present three cases of outpatient management of P. aeruginosa otolaryngological infections successfully treated with oral azithromycin, 500 mg daily ranging from 3-8 weeks, where use of fluoroquinolones was not possible due to either resistance or patient intolerance. We review the previous data supporting this clinical approach, in the hope that this will alert clinicians to this treatment option and to inspire a more thorough clinical trial evaluation of azithromycin in this environment of growing medical need.